2009
DOI: 10.1155/2009/215196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Carbon Dioxide on Two Scleractinian Corals:Porites cylindrica(Dana, 1846) andGalaxea fascicularis(Linnaeus, 1767)

Abstract: This study reveals the effect of elevated pCO 2 on Porites cylindrica and Galaxea fascicularis. The corals responded differently under elevated pCO 2 . Zooxanthellae cell density, cell mitotic index, and photosynthesis rate of P. cylindrica decreased drastically under the elevated pCO 2 . At the end of the experiment, P. cylindrica suffered from a declining calcium carbonate precipitation rate. G. fascicularis increased its respiration rate and expelled 71% of its symbiotic zooxanthellae algae under elevated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
17
2
Order By: Relevance
“…Nonetheless, we find that the skeletal densities in the low pH FOCE corals differed by less than 3% from the densities of control corals (Table S3). Furthermore, the calcification rates that we measured were comparable to or higher than rates reported in prior studies (33,34), which further demonstrates the capacity of P. cylindrica from Heron Island reef flat to calcify and grow at normal rates despite the highly variable and disparate thermal and chemical conditions in the controls and in the FOCE treatments.…”
Section: Resultssupporting
confidence: 83%
“…Nonetheless, we find that the skeletal densities in the low pH FOCE corals differed by less than 3% from the densities of control corals (Table S3). Furthermore, the calcification rates that we measured were comparable to or higher than rates reported in prior studies (33,34), which further demonstrates the capacity of P. cylindrica from Heron Island reef flat to calcify and grow at normal rates despite the highly variable and disparate thermal and chemical conditions in the controls and in the FOCE treatments.…”
Section: Resultssupporting
confidence: 83%
“…Their own experiments indicated that, at normal temperatures, there was no response to elevated pCO 2 but when temperature and pCO 2 were both elevated, calcification dropped by 50%. Yii et al (2009) found an increase in calcification rate for Galaxea fascicularis and a decrease for Porites cylindrica with increased CO 2 levels. Muehllehner & Edmunds (2008) reported a small (+5%) increase in calcification rate at 29ºC for Porites rus (n=11) and a larger (+100%) increase for Pocillopora meandrina (n=9) with increased pCO 2 ; however at 27ºC there were reductions in calcification rate for both species.…”
Section: Discussionmentioning
confidence: 87%
“…Chlorophyll a per symbiont cell did not change under ocean acidification in the experimental study of P. acuta. However, in six out of seventeen exposures in the literature, ocean acidification caused statistically significant alterations in chlorophyll a per symbiont cell (Hii et al 2009;Crawley et al 2010;Krief et al 2010;Ogawa et al 2013;Horwitz and Fine 2014). In five out of six of these cases, chlorophyll a per symbiont cell increased ( Figure 4.2b).…”
Section: Discussionmentioning
confidence: 92%
“…pCO 2 partial pressure (in µatm) was not reported in Hii et al (2009), so consequently, this value had to be calculated from the reported CO 2 content of seawater in µmol•kg -1…”
Section: Published Data Explorationmentioning
confidence: 99%
See 1 more Smart Citation